2013
DOI: 10.1111/mmi.12248
|View full text |Cite
|
Sign up to set email alerts
|

Haloferax volcanii archaeosortase is required for motility, mating, and C‐terminal processing of the S‐layer glycoprotein

Abstract: SummaryCell surfaces are decorated by a variety of proteins that facilitate interactions with their environments and support cell stability. These secreted proteins are anchored to the cell by mechanisms that are diverse, and, in archaea, poorly understood. Recently published in silico data suggest that in some species a subset of secreted euryarchaeal proteins, which includes the S-layer glycoprotein, is processed and covalently linked to the cell membrane by enzymes referred to as archaeosortases. In silico … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
65
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 39 publications
3
65
0
Order By: Relevance
“…This glycoprotein was previously thought to be anchored to the cell membrane by the intercalation of a C-terminal TM segment (15). However, we have demonstrated that this TM segment, which is part of a conserved tripartite structure, is processed in an archaeosortase A (ArtA)-dependent manner (14). In light of previous results demonstrating that this extensively studied cell wall subunit is lipid modified with archaetidic acid (2,3-di-O-phytanyl-sn-glycerylphosphate) (16)(17)(18)(19), we hypothesized that ArtA also mediates proteolysis-coupled lipid modification.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…This glycoprotein was previously thought to be anchored to the cell membrane by the intercalation of a C-terminal TM segment (15). However, we have demonstrated that this TM segment, which is part of a conserved tripartite structure, is processed in an archaeosortase A (ArtA)-dependent manner (14). In light of previous results demonstrating that this extensively studied cell wall subunit is lipid modified with archaetidic acid (2,3-di-O-phytanyl-sn-glycerylphosphate) (16)(17)(18)(19), we hypothesized that ArtA also mediates proteolysis-coupled lipid modification.…”
mentioning
confidence: 87%
“…In light of previous results demonstrating that this extensively studied cell wall subunit is lipid modified with archaetidic acid (2,3-di-O-phytanyl-sn-glycerylphosphate) (16)(17)(18)(19), we hypothesized that ArtA also mediates proteolysis-coupled lipid modification. Cells lacking ArtA exhibit a growth defect, are relatively small, and have a severe motility defect (14). While some of these phenotypes are consistent with defects that might be caused by an unstable cell wall due to the improper surface anchoring of the unprocessed SLG, H. volcanii is predicted to contain eight additional ArtA substrates, so the failure to accurately process these other substrates might also contribute to the observed phenotypes (12).…”
mentioning
confidence: 94%
See 3 more Smart Citations